The role of structural evolution in the complexation and flocculation of heavy metals by the microbial product poly-γ-glutamic acid. (December 2022) - Wang, Ling-Ling; Liu, Ya-Min; liu, Hui-Ming; Shi, Qing-Shan; Peng, Ru-Qun; Xie, Xiao-Bao
Abstract: The process and mechanism of heavy metal flocculation with extracellular polymeric substances (EPS) secreted by microorganisms, are crucial to their fate in natural environment, wastewater treatment and soil bioremediation applications. However, the structural features of EPS and the relationship between these features and the flocculation process and mechanism remain unclear. In the present study, structural features of the microbial product poly-γ-glutamic acid (γ-PGA) complexed with the heavy metal ions Pb 2+ and Cu 2+ were characterized and the evolution of these features was identified as having a key role in the flocculation process and mechanism. The secondary structure of the γ-PGA-Pb complex changed significantly, while that of the γ-PGA-Cu complex was only slightly altered. The significant structural change in γ-PGA-Pb was found to be responsible for the combination of residual COOH and Pb 2+, promoting the bridging of inter-colloids and faster growth of hydrodynamic diameter. If the conformation changed sufficiently, such as with the γ-PGA-Pb complex in the pH range 4.6–6.2, pH had no impact on the conversion ratio. The unchanged structure of γ-PGA-Cu prevented the flocculation process, although the coordination mode of γ-PGA-Cu resulted in a higher biosorption capacity. This in-depth molecular-level study provides insight into the γ-PGA flocculation mechanism, promoting the use of γ-PGA and γ-PGA producing microorganisms for application in various remediation strategies. Graphical abstract: Image 1 Highlights: Pb 2+ and Cu 2+ induced different changes in the secondary structure of γ-PGA. Biosorption does not promote Pb 2+ and Cu 2+ flocculation with γ-PGA. γ-PGA-Pb and γ-PGA-Cu are mononuclear bidentate and binuclear bidentate complexes. Structural evolution plays a key role in the γ-PGA flocculation mechanism.